Analisis Terhadap Perubahan Ketentuan Pengupahan di Indonesia Melalui Teori Maslahah Mursalah - Adawiyah, Robiatul (Jurisdictie: Jurnal Hukum dan Syariah, 2016)
Th problem of PP No. 78 year 2015 that causes the action unions which regard that PP is more side to entrepreneur and has been contradictory with labour law. To answer that problem is know the fee changes based on the PP No. 78 year 2015 if reviewed based on principle of the labour law and perspective of Maslahah Mursalah theory to see it. Ths research uses the research method yuridis normative. Th result is fee changes based on the PP No. 78 year 2015 is section 43 article (5) about component of observation KHL that is done every 5 years which before in PP No. 8 year 1981 is done every 1 year. Maslahah Mursalah Ath-Thf theory see that it is to welfare between workers, entrepreneur, and government. Concluding is provision fee in PP No. 78 year 2015 not contradict with the principle of the labour law and Maslahah Mursalah Ath-Thufi theory see that it as the frm of general welfare.Permasalahan dalam PP No. 78 Tahun 2015 disebabkan aksi serikat kerja yang merasa PP berpihak pada pengusaha dan bertentangan dengan UU Ketenagakerjaan. Untuk menjawab masalah tersebut, harus diketahui perubahan ketentuan pengupahan dalam PP berdasarkan prinsip hukum ketenagakerjaan, serta menganalisanya berdasarkan perspektif Maslahah Mursalah Ath-Thfi Hasilnya adalah, perubahan ketentuan dalam PP ialah pasal 43 ayat (5) tentang KHL yang ditinjau 5 tahun sekali, yang dalam PP No. 8 Tahun 1981 diatur 1 tahun sekali. Maslahah Mursalah Ath-Thf menganggap perubahan tersebut sebagai wujud kemaslahatan pekerja, pengusaha dan pemerintah. Hasil akhir adalah bahwa perubahan dalam PP baru tidak bertentangan dengan prinsip hukum ketenagakerjaan yang semata-mata bertujuan untuk kemaslahatan umum.